Volilni sistem iz žabje perspektive - Ribičič, Ciril (Teorija in praksa, 1999)
The author analyses the electorial system clashing in Slovenia and the system of one transferable vote of the Republic of Ireland, from the viewpoint of the voter and the influence of his/her vote on the election of representatives, on the representation of political parties in parliament, on the formation of the government and the functioning of the opposition, etc. The author gives priority to those electorial systems (German, Irish systems) which enable significant personalisation of elections without deviating from the principle of proportional representation and which strenghten the stability of the government, as well as reduce the number of parliamentary parties without leading into dual-partisanship and political polarisation ensuing which ensues from it.
Keywords: volilni sistemi; Slovenia; Slovenija; primerjalno pravo